2017
DOI: 10.1016/j.drudis.2017.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic nanoformulations for prostate cancer

Abstract: Magnetic nanoparticles (MNPs) play a vital role for improved imaging applications. Recently, a number of studies demonstrate MNPs can be applied for targeted delivery, sustained release of therapeutics, and hyperthermia. Based on stable particle size and shape, biocompatibility, and inherent contrast enhancement characteristics, MNPs have been encouraged for pre-clinical studies and human use. As a theranostic platform development, MNPs need to balance both delivery and imaging aspects. Thus, this review provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…MNPs can convert their energy to heat under the influence of an alternating magnetic field. 13 The previous studies have shown that heat-induced MNPs encapsulated in liposomes can be a good option for magnetic thermotherapy. 6 , 24 , 28 The research in this field has investigated the effect of magnetic liposomes on the cancer treatment or drug loading on the liposome.…”
Section: Resultsmentioning
confidence: 99%
“…MNPs can convert their energy to heat under the influence of an alternating magnetic field. 13 The previous studies have shown that heat-induced MNPs encapsulated in liposomes can be a good option for magnetic thermotherapy. 6 , 24 , 28 The research in this field has investigated the effect of magnetic liposomes on the cancer treatment or drug loading on the liposome.…”
Section: Resultsmentioning
confidence: 99%
“…An excellent review concerning the diagnosis, targeting, and treatment of prostate cancer by means of MNPs was published in 2017 by Chowdhury et al; the review concludes that modified MNPs that combine targeted drug delivery with MHT might represent potential future theranostic solutions for prostate cancer. Most importantly, these theranostic nanoformulations might allow the monitorization of disease progression while the treatment is ongoing based on the “see-and-treat” principle (Chowdhury et al 2017 ).…”
Section: Magnetic Nanoparticle Nanoformulations Biocompatibilitymentioning
confidence: 99%
“…Throughout the years, different types of nanosystems have been addressed in order to study their various biological applications and have a better understanding on which particles serve the human kind best in terms of serious diseases such as cancer [ 15 ]. Regarding the enhancement of PCa diagnosis and treatment, among the different types of nanoparticles studied so far are iron oxide, silver, gold, platinum, quantum dots, and liposomes [ 23 , 24 , 25 ]. The main challenges in the methods using the above-mentioned nanoparticles are to overcome their limited biodistribution, toxicity, and clearance from the excretory pathway [ 13 ] that is depicted in Table 1 .…”
Section: Nanotechnology and Its Importance In Theranosticsmentioning
confidence: 99%